Pelatihan Desain Grafis Menggunakan Canva Untuk Promosi Produk Lokal - Irfan Ali; Fatihanursari Dikananda; Ridho Nugraha; Sri Ayuningsih (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The advancement of digital technology provides significant opportunities for micro, small, and medium enterprises (MSMEs) to enhance the competitiveness of local products through engaging visual promotions. This study aims to evaluate the effectiveness of graphic design training using the Canva platform to support the promotion of local products by rural communities. The training program was conducted as part of a community service initiative focusing on improving digital literacy and design skills, especially among housewives and youth from local organizations. The program utilized a participatory approach with stages including observation, training, mentoring, and evaluation. Initial observations indicated that most participants lacked graphic design skills but showed high enthusiasm for learning. The training materials covered the basics of visual design, the use of graphic elements, and hands-on practice in creating posters, product catalogs, and social media content using Canva. Evaluation results showed significant improvement in both technical abilities and creative output among participants. Many were able to produce promotional content suitable for online publication. These findings suggest that accessible online design platforms such as Canva can effectively enhance community capacity in local product promotion. This initiative contributes to the empowerment of the village creative economy and strengthens local product identity through professional and appealing visualization. For sustainability, collaboration with related institutions and the development of local design communities are highly recommended.